Pengaruh Tingkat Pendidikan, Disiplin Kerja, dan Budaya Organisasi Terhadap Kinerja Pegawai di Badan Pengelola Keuangan dan Aset Daerah Kabupaten Sintang - Anton, Anton Reza Sianturi B11111111 (Jurnal Manajemen Update, 2017)
INFLUENCE OF EDUCATION LEVEL, WORK DICIPLINE, AND ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF EMPLOYEES IN THE FINANCIAL MANAGEMENT AND ASSETS OF SINTANG DISTRICTANTON REZA SIANTURI ABSTRACTThe financial management and assets of the sintang district makes the level of education, work discipline and organizational culture as important factors in improving employee performance. This is because, if every employee who works does not have sufficient level of education then the employee will not be able to overcome the tasks and problems that arise either internally or externally. In addition, work discipline and organizational culture are also important factors in an office or agency that can affect employee performance. If employees do not have the discipline of work then the work will not be maximized. Employees must also have a good organizational culture to improve performance, this is because to close and reduce the limitations of individual skills required the existence of organizational culture, organizational culture can also help to overcome problems arising either internally or externally. The purpose of this study was to analyze the effect of education level, work discipline and organizational culture on employee performance in the financial management and assets of sintang district. The data used in the study is primary data (from questionnaire) with samples taken 49 people. While the analytical technique used is to use multiple linear regression and hypothesis test used is t test and F test and the coefficient of determination. The analytical method used is multiple linear regression analysis using SPSS v.20.0 software.The results of data analysis show that the level of education, work discipline, and organizational culture have a positive and significant effect on the performance of employees in the Regional Financial and Asset Management Board of Sintang District. The higher the level of education an employee has, the better the performance can be. Similarly, the discipline of work and organizational culture, the better and higher work discipline and organizational culture by an employee, the more optimal performance is also generated.   Keywords: Level of education, Work Discipline, Organizational Culture and Employee Performance